Calorie Restriction Enhances Insulin-Stimulated Glucose Uptake and Akt Phosphorylation in Both Fast-Twitch and Slow-Twitch Skeletal Muscle of 24-Month-Old Rats - Sequea, Donel A. (Oxford University Press, 2012)
Calorie restriction (CR) induces enhanced insulin-stimulated glucose uptake in fast-twitch (type II) muscle from old rats, but the effect of CR on slow-twitch (type I) muscle from old rats is unknown. The purpose of this study was to assess insulin-stimulated glucose uptake and phosphorylation of key insulin signaling proteins in isolated epitrochlearis (fast-twitch) and soleus (slow-twitch) muscles from 24-month-old ad libitum fed and CR (consuming 65% of ad libitum, intake) rats. Muscles were incubated with and without 1.2 nM insulin. CR versus ad libitum rats had greater insulin-stimulated glucose uptake and Akt phosphorylation (pAkt) on T308 and S473 for both muscles incubated with insulin. GLUT4 protein abundance and phosphorylation of the insulin receptor (Y1162/1163) and AS160 (T642) were unaltered by CR in both muscles. These results implicate enhanced pAkt as a potential mechanism for the CR-induced increase in insulin-stimulated glucose uptake by the fast-twitch epitrochlearis and slow-twitch soleus of old rats.